AN IDENTIFICATION OF THE ATTITUDES OF THE SCHOOL OF HEALTH STUDENTS TOWARDS AGEISM - ÇALIŞKAN, İlknur; ELMAS, Semra (Göbeklitepe Medical Science Journal, 2022)
The study was carried out in a determinative manner to identify the attitudes of nursing and physiotherapy students that are going to give healthcare service in their work lives towards ageism. The sample of the study was constituted by 261 school of health students that agreed to take part in the study and remained in the school in the span of the study. As the data collection tool Personal Information Form and Ageism Attitude Scale was used. The data was evaluated using in SPSS 16.0 package program, the descriptive statistics Student t test, Mann Whitney U, ANOVA and Kruskal Walles tests. The average of age of the students involved in the study is 20.69±2.03. 52.5% of them are nursing students. It has been found that the Ageism Attitude Scale total grade average of the students is 82.28±8.55 and they received 32.75±4.28 in terms of limiting the life of senior citizens, 29.24±4.47 in terms of positive ageism, 17.29±3.26 in terms of negative ageism. It has been determined that school of health students have a positive attitude regarding ageism. Preparing education and consultation programs on agedness and ageism for the students that are to work with senior citizens in their work lives was recommended.